2008
DOI: 10.1016/j.jmwh.2008.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Use of Hyaluronidase to Prevent Perineal Trauma During Spontaneous Delivery: A Pilot Study

Abstract: Our objective was to compare the frequency, degree, and location of perineal trauma during spontaneous delivery with or without perineal injections of hyaluronidase (HAase). This was a randomized, controlled pilot study, conducted in a midwife-led hospital birth center in São Paulo, Brazil. Primiparous women (N = 139) were randomly assigned to an intervention group (HAase injection, n = 71) or to a control group (no injection, n = 68). Significant differences were noted between the two groups in frequency of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 21 publications
(50 reference statements)
1
24
1
5
Order By: Relevance
“…In two other studies, the authors afirmed that there were less cases of second degree laceration and more parturitions with intact perineum in black women (11)(12)(13)(14) . Age was the next variable, and studies confirmed the absence of scientific evidence to associate perineal trauma to the maternal age, and emphasized the lack of significance in association between these variables (11,(14)(15)(16) , confirming the findings of this study.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…In two other studies, the authors afirmed that there were less cases of second degree laceration and more parturitions with intact perineum in black women (11)(12)(13)(14) . Age was the next variable, and studies confirmed the absence of scientific evidence to associate perineal trauma to the maternal age, and emphasized the lack of significance in association between these variables (11,(14)(15)(16) , confirming the findings of this study.…”
Section: Resultsmentioning
confidence: 91%
“…In a transversal study about factors related to perineal trauma in normal parturition in nulliparas (10,12) , there was a prevalence of white women experiencing perineal trauma, but not at a statistically relevant level. In two other studies, the authors afirmed that there were less cases of second degree laceration and more parturitions with intact perineum in black women (11)(12)(13)(14) .…”
Section: Resultsmentioning
confidence: 96%
“…This is a common event that affects women across a variety of international settings (Barreto-Scarabotto and Gonzalez-Riesco, 2008;Kettel et al, 2010;Ismail et al, 2013;Smith et al, 2013). Despite the frequency of the event there is a dearth of research which relates to women's experience of perineal suturing or the clinician's decision to suture.…”
Section: To Pain Associated With Suturing Second Degree Perineal Tearmentioning
confidence: 99%
“…A small Brazilian study (Scarabotto and Riesco 2008) considered the use of hyaluronidase injections into the perineum during second stage and found that the incidence and severity of perineal trauma was significantly reduced in the intervention group. This method would need to be researched on a sample, both larger in number and suitable to apply results to the UK before practice could be adapted.…”
Section: What Techniques Are Proven To Improve Outcome?mentioning
confidence: 99%